Local exchange networks in the Horn of Africa: a view from the Mediterranean world (third century B.C. -sixth century A.D.) - (:unkn) unknown (My University, 2020)
The ancient history of the Horn of Africa1 is closely tied to to Axum’s glorious destiny. From the first century A.D. onwards this modest polity settled on the Abyssinian plateau gradually evolved into a kingdom whose power extended westward to Nubia and Meroe, and eastward as far as the Red Sea – an anonymous king even boasted of reaching the African coast of the Gulf of Aden. The Axumite authority also expanded across the Red Sea more than once, temporarily subjugating the South Arabian kingdoms of Saba and Ḥimyar. With the port of Adulis, Axum judiciously took advantage of its position on the Red Sea to become a prominent trading state between the third and the sixth centuries A.D. Axum’s prestige owes much to this key role in the Western Indian Ocean trade system. Due to this rather understandable bias in favour of Axum’s long-range trade activity, the more humble local forms of trade which flourished throughout the Horn of Africa over centuries are generally overlooked. These local exchange networks, however, were the building blocks of the whole Indian Ocean commerce, which was entirely supported by this low scale activity and its agents. As such local networks are worth being investigated for their own sake. The longue durée perspective is also required, for they were just as subject to changes and disruptions over centuries as the large scale trade patterns.This paper aims at extensively collecting the Greek and Latin documents handed down to us . The truth is that this evidence does not amount to much, many texts being lost. In spite of not depicting the local trade in the Horn in detail, this material provides nonetheless an acceptable picture of the local inland and maritime circuits (the sea routes between the Horn and southern Arabia obviously fall within the scope of this paper). Thus it is hoped that this paper will properly complement the past and future investigations carried out by archaeologists focusing on the same issue.
Keywords: African Research